Artificial intelligence-assisted project-based learning: Examining the interaction with learning creativity on the students’ digital content outcomes - Rudi Hartono; Salsabila Adrisdityas Candra Rifani; Muktiono Waspodo (UIN Raden Mas Said Surakarta, 2026)
Despite the rapid integration of artificial intelligence (AI) in education, limited empirical evidence compares the effectiveness of AI-assisted project-based learning (PjBL) and problem-based learning (PBL) while considering students’ learning creativity in digital content production. This study aims to examine the effects of AI-assisted PjBL and AI-assisted PBL, as well as their interaction with students’ learning creativity, on learning outcomes in digital content production. The study employs a 2×2 quasi-experimental factorial design, in which factor (A) represents the learning model (AI-assisted PjBL and AI-assisted PBL) and factor (B) represents learning creativity (high and low). The population consists of eighth-grade students at the junior high school level. The findings address four hypotheses: (1) there is a significant difference in learning outcomes between students receiving AI-assisted PjBL and those receiving AI-assisted PBL (Sig. 0.043 < 0.05); (2) there is a significant interaction effect between AI-assisted learning models and learning creativity (Sig. 0.000 < 0.05); (3) students with high creativity who receive AI-assisted PjBL achieve higher learning outcomes than those receiving AI-assisted PBL (Sig. 0.000 < 0.05); and (4) students with low creativity who receive AI-assisted PjBL demonstrate lower learning outcomes than those receiving AI-assisted PBL (Sig. 0.000 < 0.05). These findings indicate that AI-assisted PjBL and learning creativity enhance students’ learning outcomes in producing creative digital content, particularly for students with high learning creativity. This study contributes empirical evidence to the integration of AI in junior high school computer science education.